Livelihoods and the Play of Eviction in the Akuarium Neighborhood - Khudi, Achmad Firas (Asia Social Issues, 2023)
The Jakarta government evicted an urban community of Akuarium in 2016, which caused socio-economic and immaterial difficulties. Such difficulties appear from destroyed livelihoods but instigated a kind of play in the community. A theory of urban play envisages how the community responds and utilizes failed development projects drawing from the practices of graffiti, car jockeys, and navigation of traffic jams. The research method includes field and internet ethnography for around one year. The research uncovers worsening precarious life, plunging the Akuarium community from poverty to severity. The severity includes massive loss of occupations, and houses, unexpected eviction costs, the loss of markets and crowdedness for market support, and the multi-source of income as in small shops and housing rental. The Akuarium people respond with an urban play as a small tactic for survival, responding to violence and difficulty. The urban play includes bringing appliances, mobilizing small mobs, and opening their clothes with only underwear covering the breasts and sexual organs to seek the empathy of apparatuses for stopping the eviction. Akuarium people showed urban play as a claim of space without aggression and a last-resort weapon to sustain urban life, an archetype of resistance through spatial practice.